Randomized controlled trial of three burns dressings for partial thickness burns in children. Issue 5 (August 2015) - Gee Kee, E.L.; Kimble, R.M.; Cuttle, L.; Khan, A.; Stockton, K.A.
Highlights Three burns dressings for partial thickness burns in children were compared. Wound re-epithelialization time was significantly faster in children treated with Mepilex Ag™. Dressings with silicone interfaces had significantly lower pain levels at dressing changes. No infections were detected for the course of the study.